Kondisi Rumah sebagai Faktor Risiko Tuberkulosis Paru Pada Balita yang Berkunjung Di BP4 Semarang Tahun 2002 - Fitriatun, Siti; Sulistiyani, Sulistiyani; Nurjazuli, Nurjazuli (Jurnal Kesehatan Lingkungan Indonesia, 2002)
Background : In Indonesia, tuberculosis are still a major health problem and the major cause of death among infectious diseases. In Semarang 10% of Patient who visited in BP4 (Lungs Diseases Policlinic) were children under five year-old with low social economic level and poor sanitation in their houses. The objective of this study is to determine the relationship between the house condition and the occurrence of tuberculosis among children under five year-old. Variables of the house condition measured in this study were lighting, humidity, temperature, ventilation, and house occupant density. Methods : This study was a case control study. Samples were 65 children who had suffered from tuberculosis andÂ  cared in BP4 Semarang as the study group, and 65 healthy children who had the same characteristic as the control group. Analysis was conducted by calculating crude odds ratio (OR) and applying multiple logistic regression. Results :The study shows that average of lighting is 88,34 lux, humidity is 77,42 %, temperature is 29,43 0C, large of ventilation is 9,58 % and house occupant density is 4 person per house (25,4 %). Risk factor that significantly associated with the occurrence of tuberculosis among children under five year-old is the house occupant density ( p value = 0,0267 ), odds ratio 2,9219. Conclusion : children under five year-old who live in the house with high level of density of occupancyÂ  have risk to get tuberculosis, 2,9219 time compared to those who live in low level of density. Key Word : House condition, children under five year-old, tuberculosis.